Paecilomyces variotii as an emergent pathogenic agent of pneumonia - Assmann, Bruna Steiner (2013)
Paecilomyces variotii is a commonly occurring species in air and food, and it is also associated with many types of human infections. Pneumonia due to Paecilomyces variotii has been rarely reported in the medical literature. The authors report a 48-year-old patient with refractory lymphoma who underwent allogenic hematopoietic cell transplantation and developed pneumonia due to Paecilomyces variotii.They also review the published case reports of pneumonia caused by this fungus.